2017
DOI: 10.1007/s00703-017-0530-0
|View full text |Cite
|
Sign up to set email alerts
|

Multifractal analysis of the drought area in seven large regions of China from 1961 to 2012

Abstract: Based on a monthly drought index, the Standardized Precipitation Index (SPI), we investigate the multifractality of monthly drought areas in seven major regions in China from 1961 to 2012 using multifractal detrended fluctuation analysis. The results show that multifractality is evident in the monthly time series for all seven regions, but its strength varies between areas. From the numerical results, we further examine the stationarity and persistence of the time series in the seven drought areas. The charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 85 publications
(67 reference statements)
1
21
0
Order By: Relevance
“…The plot between h(q) versus q is helpful to assess the multifractality [13]. To represent the scaling exponent, one unit addition is necessary by the relation (q) = h(q) + 1 , where the behaviour of the plot remains the same.…”
Section: Mf-dfa Of Daily Streamflowmentioning
confidence: 99%
See 2 more Smart Citations
“…The plot between h(q) versus q is helpful to assess the multifractality [13]. To represent the scaling exponent, one unit addition is necessary by the relation (q) = h(q) + 1 , where the behaviour of the plot remains the same.…”
Section: Mf-dfa Of Daily Streamflowmentioning
confidence: 99%
“…Asymmetric index (R) is a useful parameter for multifractal analysis [13], which can be derived from the multifractal spectrum. It is obtained by following relation: value is positive, which shows that the largest fluctuations are more frequent than smallest fluctuations in the streamflow series of all stations.…”
Section: Mf-dfa Of Daily Streamflowmentioning
confidence: 99%
See 1 more Smart Citation
“…As the drought indices are quantified based on hydro‐meteorological variables like precipitation, evapotranspiration and streamflow, it is logical to suspect fractal properties in such derived indices also. However, the multifractal analysis of hydrological extremes like floods or droughts is really scarce in literature while in the past decade, few studies in this direction were reported (Hou et al , ; ; Zhang et al , ). Tatli () determined persistence in the PDSI of 1966–2010 period over Turkey by determination of scaling (Hurst, H) exponent using classical rescaled range analysis, but did not estimate other multifractal properties of the series.…”
Section: Introductionmentioning
confidence: 99%
“…The high values of the Hurst exponent in all the regions were attributed to the possible association between drought and the large‐scale atmospheric circulations. Hou et al () performed multifractal characterization of drought from seven regions in China considering the SPI series, based on monthly rainfall data of 1961–2012 period. The SPI series of North and North West regions of China showed short‐term persistency while in the remaining regions, the SPI showed LTP.…”
Section: Introductionmentioning
confidence: 99%